PENGARUH KECERDASAN EMOSIONAL DAN KEPRIBADIAN TERHADAP KEPEMIMPINAN KEPALA MADRASAH DI KABUPATEN AGAM - Ali Mutasar; Masril Masril; David David; Suswati Hendriani; Wahidah Fitriani (IAIN Batusangkar, 2019)
The problem of this thesis related to the emotional intelligence and personality of the headmaster in state of madrasah at Agam Regency. The purpose of this thesis is to: 1) to know how much the influence of emotional intelligence in the leadership of the headmaster of Madrasah in Agam regency, 2) to Know how much the influence of personality of the headmaster of the leadership of Madrasah in Agam regency, 3) to Know how much the influence of emotional and personality intelligence in the headmaster of the leadership of Madrasah in Agam regency. The research method used descriptive analysis with quantitative approach through the technique of correlation of the data analysis and regression by using parametric statistics. Data was taken by using questionnaire. The population of this reseaerch were MTsN teachers in Agam Regency, the total of the population is 450 people, with the sample of this research were 85 teachers. The results of this research , stated that two independent variables of emotional intelligence and personality had a significant influence on the leadership of the headmaster of madrasah in Agam regency. Thus the hypothesis which stated that there is an influence of emotional intelligence on the leadership of the headmaster of madrasah is accepted. Likewise, the hypothesis that stated there is an influence of personality on the leadership of the headmaster is also accepted. Emotional intelligence and personality had influence of the leadership of the headmaster in madrasa at Agam Regency.